Wanted Dead or Alive: Skeletal Structure Alteration of Cold-Water Coral Desmophyllum pertusum (Lophelia pertusa) from Anthropogenic Stressors - Krueger, Erica Terese; Hoey, David; Taylor, David; O'Reilly, Peter; Crowley, Quentin; Krueger, Erica (My University, 2023)
Ocean acidification (OA) has provoked changes in the carbonate saturation state that may alter the formation and structural biomineralisation of calcium carbonate exoskeletons for marine organisms. Biomineral production in organisms such as cold-water corals (CWC) rely on available carbonate in the water column and the ability of the organism to sequester ions from seawater or nutrients for the formation and growth of a skeletal structure. As an important habitat structuring species, it is essential to examine the impact that anthropogenic stressors (i.e., OA and rising seawater temperatures) have on living corals and the structural properties of dead coral skeletons; these are important contributors to the entire reef structure and the stability of CWC mounds. In this study, dead coral skeletons in seawater were exposed to various levels of pCO2 and different temperatures over a 12-month period. Nanoindentation was subsequently conducted to assess the structural properties of coral samples’ elasticity (E) and hardness (H), whereas the amount of dissolution was assessed through scanning electron microscopy. Overall, CWC samples exposed to elevated pCO2 and temperature show changes in properties which leave them more susceptible to breakage and may in turn negatively impact the formation and stability of CWC mound development.
PUBLISHED
Keywords: biomechanics; biomineralisation; climate change; cold-water coral; porosity; ocean acidification; Nanoscience & Materials; Smart & Sustainable Planet; Biodiversity; CLIMATE CHANGE; Earth Sciences for Climate Research; Mechanical Engineering; Other; Education